Artificial Intelligence in Public Relations and Communication Management: Perspectives of Ghanaian Professionals - Albert Anani-Bossman; Noel Nutsugah; Justice Issah Abudulai (Communicare)
Artificial intelligence (AI) is presently transforming society and industries with significant implications for the public relations and communication profession. However, scholarship on this subject in Africa is lacking. This paper addresses this gap by investigating AI in the public relations and communication management industry in Ghana. It focuses on the knowledge, adoption, and impact of AI, as well as the perceived risks and challenges associated with the application of AI. The study used the quantitative method to gather data from 275 professionals. Results revealed that professionals have a limited understanding of AI despite their knowledge of the concept. Communication professionals believe AI will impact the profession, their department, and how they work. However, they did not foresee any challenges or risks associated with applying AI (e.g. competency in using AI, motivation to use AI, and loss of jobs). The result points to the need for professionals to increase their knowledge and understanding of AI. There is also the need for public relations scholars in Ghana and Africa to begin serious discussions on this issue.